CD4+FOXP3+cells produce IL-10 in the spleens of dogs with visceral leishmaniasis - Oliveira Silva, Kathlenn Liezbeth [UNESP]; Andrade, Mariana M. C. de [UNESP]; Melo, Larissa M. [UNESP]; Perosso, Juliana [UNESP]; Vasconcelos, Rosemeri O. [UNESP]; Munari, Danisio P. [UNESP]; Lima, Valeria M. F. [UNESP] (Elsevier B.V., 2014)
Visceral Leishmaniasis (VL) is caused by intracellular parasites of the genus Leishmania that affect humans and several animal species. Dogs are one of the main urban reservoirs of the parasite and play a central role in the transmission cycle to humans via sandflies. Studies concerning the immune response in dogs with VL have demonstrated that protective immunity is associated with cellular immune response, while disease progression is associated with humoral response and IL-10 and TGF-beta production. The study aimed to evaluate IL-10 and TGF-beta production by regulatory T (Treg) cells in the blood and spleen of dogs naturally infected by Leishmania spp. and correlate this with parasite load. Five healthy dogs and 29 dogs with proven infection were selected for the study group. Real-time PCR was used to quantify parasite load and confirm infection by Leishmania spp. Treg cells producing IL-10 and TGF-beta were quantified using flow cytometry. An increase in IL-10 production by Treg cells was verified in the spleen of dogs naturally infected by Leishmania spp. Concurrently, a decrease in the total number of T cells in these dogs was verified compared with healthy dogs. No association was determined between parasite load and the percentage of spleen Treg cells producing IL-10 and TGF-beta. These findings suggest that Treg cells are an important source of IL-10 in the spleen, participating in immune response modulation, while the reduced percentage of these cells in infected dogs could be attributed to persistent immune activation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Leishmania; Dog cytokines; Regulatory T cells; IL-10; TGF-beta